A mid-16th century carvel-built ship from Mukran, Jasmund-Peninsula, Island of Rügen, Germany - Alexiou, Konstantinos; Auer, Jens; Belasus, Mike (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
The 16th century ‘Mukran wreck’ is one of the earliest carvel-built ships found in Germany. Naval armament found in the vicinity of the site and traces of fire within the remains may relate the wreck to a hostile encounter between a joined squadron of Danish vessels and ships from the Hanseatic town of Lübeck with Swedish ships in 1565 during the Nordic Seven Years’ War (1563‒1570). In 2016 and 2017 a detailed investigation and recording of the wreck was carried out. The wreck represents an important source for the understanding of the development of carvel shipbuilding in northern Europe.